Nature : and other essays - Emerson, Ralph Waldo, 1803-1882 (Gibbs Smith, 2019)
A collection of essays from the father of the American transcendentalism. Essays include "Nature" (1836) and Emerson's first series, published in 1841: "History," "Self-Reliance," "Compensation," "Spiritual Laws," "Love," "Friendship," "Prudence," "Heroism," "The Over-Soul," "Circles," "Intellect," and "Art."